Nursing care plans & documentation : nursing diagnoses and collaborative problems - Carpenito-Moyet, Lynda Juall. 4 0 16; 5 (Philadelphia : Lippincott Williams & Wilkins, 2004)
Provides interventions and rationales for both nursing diagnoses and collaborative problems, and identifies diagnostic clusters that group the most likely diagnoses and problems for each clinical situation.
Includes bibliographical references (p. 1051-1071) and indexes.
Adult;Adult
Keywords: 2 -- 0; 6; Nursing care plans.;Nursing assessment.;Nursing diagnosis.;Patient Care Planning.;Nursing Process.;Nursing Records.;Nursing.;Nursing assessment.;Diagnosis.; 20; 2